Hikayat Hang Tuah pemahaman dan penghayatan beberapa aspek - Ramli ISin. (Kuala Lumpur Fajar Bakti Sdn. Bhd., 1994)
Interpretations of characters and events in the Hikayat Hang Tuah, a Malay classic.
Includes bibliographical references.
In Malay.
Keywords: Hikayat Hang Tuah